AKURASI OXYGEN SATURATION (SpO2) SEBAGAI PREDIKTOR MORTALITY PADA KLIEN CEDERA KEPALA - Riki Ristanto; Amin Zakaria (Jurnal Kesehatan Mesencephalon, 2018)
Cerebral hypoxia is secondary injury which affects the mortality of clients with Trauma Brain Injury (TBI). One component of respiration that can be used to monitor the occurrence of cerebral hypoxia is oxygen saturation (SpO2). The purpose of this study was to analyze the accuracy of oxygen saturation as a predictor of mortality in head injury clients. This study is an analytic observational with retrospective cohort design. The population is all head injury medical records from January to December 2017 at the hospital. dr. Iskak Tulungagung. A total of 150 samples were selected according to inclusion and exclusion criteria. The dependent variable in this study was the mortality of the head injury client in seven days of treatment and the independent variable was the value of SpO2 in the ED triage data in the client's medical record. The results of the Mann-Whitney test analysis showed that the SpO2 variable had a significant relationship with the mortality of the head injury client (p value = 0.000). Logistic regression test shows that the SpO2 has sensitivity = 0.907 (90.7%), specificity = 0.881 (88.1%), Positive Predictive Value (PPV) = 0.951 (95.1%), and Negative Predictive Value (NPV) = 0.787 (78.7%) with predictive accuracy capability = 90%. Oxygen Saturation is an accurate predictor (90% accuracy) of the mortality of the head injury client.Keywords: Mortality, Client Head Injury, Accuracy, Oxygen Saturation.